2021
DOI: 10.4239/wjd.v12.i9.1426
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-4 inhibitor-induced autoimmune diseases: Current evidence

Abstract: Dipeptidyl peptidase-4 inhibitors (DPP-4i) have an important place in the management of type 2 diabetes. The DPP-4 enzyme is ubiquitously distributed throughout the human body and has multiple substrates through which it regulates several important physiological functions. DPP-4 regulates several immune functions, including T-cell activation, macrophage function, and secretion of cytokines. Studies have reported an increase in autoimmune diseases like bullous pemphigoid, inflammatory bowel disease, and arthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…However, given the lower incidence of certain autoimmune disease, limited evidences are accessible. Case reports and retrospective studies of DPP4i utilization in T2DM patients demonstrated an association between the use of DPP4i and bullous pemphigoid, a severe autoimmune skin disease (18,(173)(174)(175)(176)(177). Importantly, DPP4iinduced bullous pemphigoid does not remit fully after withdrawal of DPP4i, suggesting that DPP4i induces and aggravate the process of bullous pemphigoid rather than a reversible side effect of DPP4i (18).…”
Section: Dpp4 In Other Autoimmune Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, given the lower incidence of certain autoimmune disease, limited evidences are accessible. Case reports and retrospective studies of DPP4i utilization in T2DM patients demonstrated an association between the use of DPP4i and bullous pemphigoid, a severe autoimmune skin disease (18,(173)(174)(175)(176)(177). Importantly, DPP4iinduced bullous pemphigoid does not remit fully after withdrawal of DPP4i, suggesting that DPP4i induces and aggravate the process of bullous pemphigoid rather than a reversible side effect of DPP4i (18).…”
Section: Dpp4 In Other Autoimmune Diseasesmentioning
confidence: 99%
“…Case reports and retrospective studies of DPP4i utilization in T2DM patients demonstrated an association between the use of DPP4i and bullous pemphigoid, a severe autoimmune skin disease (18,(173)(174)(175)(176)(177). Importantly, DPP4iinduced bullous pemphigoid does not remit fully after withdrawal of DPP4i, suggesting that DPP4i induces and aggravate the process of bullous pemphigoid rather than a reversible side effect of DPP4i (18). Although the exact mechanisms underlying DPP4i-associated bullous pemphigoid is currently unclear, the breakdown of immunotolerance of BP180, the major autoantigen of bullous pemphigoid, might be a key reason.…”
Section: Dpp4 In Other Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis could be supported by the previous observation that all severe combined immunodeficiency patients and immunodeficient mice have reduced levels of sDPP4 [ 13 ]. Furthermore, additional evidence on the effect of low DPP4 levels on an overall reduced immune effector response is supported by the multiple DPP4 inhibitors approved for therapeutic use in different autoimmune diseases [ 36 ]. DPP4 inhibitors are used to treat autoimmune related diabetes mellitus in children and adults as well as autoimmune encephalomyelitis [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have evaluated the association of different DPP-4i with overall autoimmune diseases directly, although age as an important determining factor of autoimmunity is associated with DPP-4i use ( 10 14 ). In our case, he was treated with DPP-4i for T2DM until the onset of DPP-4i-related BP.…”
Section: Discussionmentioning
confidence: 99%